PENGARUH MODEL DISCOVERY LEARNING TERHADAP HASIL BELAJAR SISWA PADA MATA PELAJARAN PAI KELAS VII DI SMP PTI PALEMBANG - Fitri Anggraini; Karomah; Arvin Efriani (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Islamic Religious Education (PAI) learning at the junior high school level often still relies on conventional patterns that position teachers as the sole source of information, causing students to remain passive and achieve suboptimal learning outcomes. This condition necessitates the application of the discovery learning model as an alternative student-centered approach. This study aims to analyze the extent to which the discovery learning model influences student learning outcomes in PAI subjects for seventh graders at SMP PTI Palembang. A quantitative approach was employed using a pre-experimental one group pretest-posttest design. A total of 44 students were selected through simple random sampling from a population of 50. The research instrument consisted of 20 multiple-choice items administered before and after the intervention. Data were analyzed using the paired sample t-test via SPSS. Results showed an increase in mean scores from 60.11 at the pretest stage to 87.39 at the posttest stage. Statistical testing yielded a t-value of 44.127 with a significance level of 0.000, far exceeding the t-table value of 2.017 at α = 0.05. These findings confirm that the discovery learning model significantly enhances PAI learning outcomes. In conclusion, this model is worthy of continuous integration into PAI learning processes at the junior high school level.